Digital Transformation of Educational Management Through an Android-Based Smart Learning System to Enhance Students' Islamic Education Literacy - Wahyu Sulistianing Budi; Mita Sari; Rizkia Melinda (YHMM PUBLISHING, 2026)
Digital transformation in education encourages schools to adopt innovative learning technologies that improve instructional quality and students' literacy. This study aims to develop and implement an Android-Based Smart Learning System to enhance Islamic Education Literacy among students at SMP Muhammadiyah 2 Gisting. The research employed a Research and Development (R&D) approach using the Waterfall Software Development Life Cycle (SDLC), including requirement analysis, system design, implementation, and testing. Data were collected through interviews, observations, surveys, and literature reviews. The developed application integrates learning materials, interactive quizzes, learning outcome evaluation, activity monitoring, and discussion features into a single Android platform. The implementation results indicate consistent improvement in students' achievement in Islamic Education, with average scores increasing from 72 to 78 in Grade VII, 74 to 80 in Grade VIII, and 76 to 83 in Grade IX. These findings demonstrate that the proposed system improves learning effectiveness, student engagement, and Islamic education literacy through an interactive digital learning environment. The study contributes an Android-based educational management model that supports sustainable digital transformation in secondary education.